Lo spettacolo senza riforma La compagnia del San Samuele di Venezia (1726-1749) - Galletti, Lorenzo (Premio Ricerca «Città di Firenze», 2016)
The San Samuele theatre company from Venice constitutes a perfect example of the extraordinary vitality of the early-eighteenth-century troupes, before the success of Carlo Goldoni's dramaturgy. Reconstructing the chronology of the training activity led by the theatre company manager Giuseppe Imer makes it possible to observe the extraordinary versatility of the actors from the Commedia dell'Arte, and the breadth of a repertoire which, between 1726 and 1749, spaced from dramas to musical interludes, passing through the "canovacci" of the commedia all'improvviso and tragedies. Thanks to unpublished documents and to a critical analysis of the repertoires, the author appoints the actors as the main protagonists of the spectacular Venetian scene, and offers important updates on the migrations of troupes in the second quarter of the 18th century.